2008
DOI: 10.1111/j.1462-2920.2008.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the mosquito larvicidal activities of toxins from Bacillus thuringiensis ssp. israelensis

Abstract: SummaryComparing activities of purified toxins from Bacillus thuringiensis ssp. israelensis against larvae of seven mosquito species (vectors of tropical diseases) that belong to three genera, gleaned from the literature, disclosed highly significant variations in the levels of LC50 as well as in the hierarchy of susceptibilities. Similar toxicity comparisons were performed between nine transgenic Gram-negative species, four of which are cyanobacterial, expressing various combinations of cry genes, cyt1Aa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 80 publications
1
37
0
2
Order By: Relevance
“…No data are given on the mosquitocidal activity of HS18-1 although weak activity against Aedes aegypti was found for the recombinant Cry4Cb1 and Cry30Ga toxins. Although we have yet to fully characterize all the toxins present in the Bt S2160-1 strain, or to establish whether there may be synergistic interactions between them as observed for Bti (Chilcott and Ellar, 1988;Otieno-Ayayo et al, 2008), we suggest that this strain has potential as an alternative to Bti for mosquito control. Fig.…”
Section: Discussionmentioning
confidence: 89%
“…No data are given on the mosquitocidal activity of HS18-1 although weak activity against Aedes aegypti was found for the recombinant Cry4Cb1 and Cry30Ga toxins. Although we have yet to fully characterize all the toxins present in the Bt S2160-1 strain, or to establish whether there may be synergistic interactions between them as observed for Bti (Chilcott and Ellar, 1988;Otieno-Ayayo et al, 2008), we suggest that this strain has potential as an alternative to Bti for mosquito control. Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, they synergize with and overcome resistance to mosquito larvicidal Cry proteins by functioning as a Cry membrane bound receptor. At high concentrations, due to their high affinity to lipids, these toxins can act as detergents by rupturing the cell membrane [6, 7, 14]. Additionally, the chitinase chi gene has been associated with enhanced mosquitocidal activity of Bt strains suggesting further synergism with the cyt and cry genes [7].…”
Section: Introductionmentioning
confidence: 99%
“…strain PCC 7120) that express one or a combination of genes for mosquito larvicidal proteins from Bacillus thuringiensis subsp. israelensis (26). …”
Section: Discussionmentioning
confidence: 99%
“…strain PCC 7120 and demonstrated that Int catalyzes site-specific excision whether its substrate is located on a plasmid or on the chromosome. This system can thus be used as a novel model for simple and efficient genome manipulations in cyanobacteria, in particular, the removal of genes conferring antibiotic resistance, which are unacceptable for applied purposes in transgenic organisms (26).…”
mentioning
confidence: 99%